2004
DOI: 10.1007/bf02931539
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofCandida strains in cases of paronychia

Abstract: A total of 43 patients, 11 males and 32 females, with paronychia of the fingernails were examined for the presence of Candida spp. The yeast species isolated were identified using standard laboratory methods, including germ-tube production, morphology on rice agar with Tween 80, and mainly fermentation and assimilation of saccharides. In the male group, two Candida species were detected: C. albicans as the dominant species in 9 patients and C. parapsilosis in 2 cases. Similarly, C. albicans was the prevalent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For example, biofilm production by Candida in wound healing promotes a chronic state of inflammation by creating a physical barrier and providing the wound with low oxygen and low pH, in turn delaying the wound-healing process ( 61 ). Candida can also lead to localized long-term inflammatory processes, such as vaginitis ( 62 ), stomatitis ( 63 ), and paronychia ( 64 ). Of particular relevance is that the yeast often colonizes and infects immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, biofilm production by Candida in wound healing promotes a chronic state of inflammation by creating a physical barrier and providing the wound with low oxygen and low pH, in turn delaying the wound-healing process ( 61 ). Candida can also lead to localized long-term inflammatory processes, such as vaginitis ( 62 ), stomatitis ( 63 ), and paronychia ( 64 ). Of particular relevance is that the yeast often colonizes and infects immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Gram negative bacteria in patients with diabetes was also reported by several groups. These included E. coli 0.72-4.2% (19,25,26), Proteus (Proteus vulgaris in 4.2%) (12,19,25,26), Pseudomonas aeruginosa at rates of 1.3-7.2% (12,14,18,26,27), Klebsiella at rates of 3.5-7% (9,12,19,25,26,27), Enterobacter in 1.9-5.6% (9,12,19,28), and Aerobacter aerogens in 0.72% (14). Klebsiella was the most common Gram negative organism along with staphylococcus species in mixed infection by Jalil et al (20) (10).…”
Section: Discussionmentioning
confidence: 99%
“…Connor et al(28) reported the presence of Gram-negative organisms in 31% including Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris, and species of Klebsiella, Serratia, Haemophilus, Enterobacter, Eikenella, Pasteurella, and Neiserria. Dorko et al(27) reported the presence Neisseria spp. Most authors report the role predominantly of S. aureus in hand infection but with different percentage(14,19,22,26,28).…”
mentioning
confidence: 99%
“…Connor et al [11] reported Gram-bacteria in 31% including Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris, Klebsiella, Serratia, Haemophilus, Enterobacter, Eichenella, Pasteurella and Neisseria. Dorko et al [12] reported Neisseria spp., Staphylococcus Coagulase negative between 5.7% and 12.6% (8); Streptococcus spp in 5.6-16% [2]. Staphylococcus β-haemolyticus were mostly S. pyogenes between 3.6 and 12.5% [2].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Staphylococcus β-haemolyticus were mostly S. pyogenes between 3.6 and 12.5% [2]. Dorko et al [12] reported streptococcus α-haemolyticus in 22.4%. Not-β-haemolyticus S.Viridians were found in 1.3% [7], 2.16% [7].…”
Section: Review Of the Literaturementioning
confidence: 99%